2013
DOI: 10.1167/iovs.12-10278
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Refractive Changes Associated with Myopia Progression

Abstract: PURPOSE.To evaluate the changes in peripheral refraction profiles associated with myopia progression and treatment modalities used in the Cambridge Anti-Myopia Study. METHODS.One hundred and seventy-seven myopes in the age range of 14 to 22 years were enrolled in the study. The mean spherical equivalent refractive error was À3.12 6 1.87 diopters (D) and the refractive error of each participant was corrected with contact lenses. The participants were randomly assigned to one of four treatment groups, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 49 publications
2
36
0
2
Order By: Relevance
“…53,54 No difference between peripheral refraction profiles were found between treatment groups in an increased CAMS cohort including subjects with negative spherical Facility rates at distance and near for vision training (VT) treatment and control groups, over the duration of the trial (one VT control subject had missing facility rate data at the 24-month visit) Distance aberration at baseline, 55 suggesting that peripheral defocus was not a factor in progression differences seen between treatment groups in this study.…”
Section: Discussionmentioning
confidence: 71%
“…53,54 No difference between peripheral refraction profiles were found between treatment groups in an increased CAMS cohort including subjects with negative spherical Facility rates at distance and near for vision training (VT) treatment and control groups, over the duration of the trial (one VT control subject had missing facility rate data at the 24-month visit) Distance aberration at baseline, 55 suggesting that peripheral defocus was not a factor in progression differences seen between treatment groups in this study.…”
Section: Discussionmentioning
confidence: 71%
“…Peripheral oblique astigmatism J 45 was much smaller than peripheral regular astigmatism J 180 along the horizontal and vertical fields, and was linearly related to peripheral angle 12. Radhakrishnan et al 13 reported that initial J 45 astigmatism at 20° and 30° in the temporal field was significantly correlated with myopia progression over 2 years. These findings indicate that peripheral astigmatism may play a role in refractive development.…”
Section: Introductionmentioning
confidence: 98%
“…Mutti et al, amongst others [4][5][6], also demonstrated that there is an association between myopia in children and relative peripheral hyperopia [7].…”
Section: Introductionmentioning
confidence: 99%